Essence of the Bobath concept in the treatment of children with cerebral palsy. A qualitative study of the experience of Spanish therapists. (2nd January 2022) - Farjoun, Naama; Mayston, Margaret; Florencio, Lidiane Lima; Fernández-De-Las-Peñas, Cesar; Palacios-Ceña, Domingo
ABSTRACT: Objective : The aim was to explore the experiences of a group of Spanish physical therapists who apply the Bobath concept in the treatment of children with cerebral palsy, specifically to identify the components they experience as core and essential to the Bobath concept. Design : A qualitative phenomenological study. Methods : This study used purposive sampling. Non-structured interviews were carried out with 10 Spanish Bobath-trained physical therapists who treat children with cerebral palsy. Thematic analysis was applied. Results : Five themes regarding the essence of the Bobath concept emerged: 1) "normal movement" as a guide; 2) a "global" concept; 3) observation; 4) the centrality of tone; and 5) working with families. Within these themes, additional principles were reflected cross-sectionally, such as therapy being a continuous process of assessment and treatment, the application of principles of motor learning, and the importance of carryover of treatment into function. Conclusions : The results demonstrated themes traditionally identified as core to the Bobath concept, including working with families, which is also considered integral to the approach. The study participants used outdated terminology at times when discussing tone and movement. However, they reported that they no longer adhere to the theoretical perspective of pathological reflexes and reflex/tone inhibition. This study provides insight into how treatment of children with cerebral palsy based on the Bobath concept is experienced by a group of Spanish physiotherapists, who identified five main themes that they perceive as essential. The results provide grounds for further research into the application of the Bobath concept in children.